IDNLearn.com is your go-to resource for finding expert answers and community support. Get the information you need from our community of experts who provide accurate and comprehensive answers to all your questions.

Let f(x) =4x-1 and g(x) = 2x^2 + 3 (fg)(x) , f/g(x), g/f(x)

Sagot :

f(x) = 4x - 1
g(x) - 2x² + 3

(f · g)(x)
(f · g)(x) = (4x - 1)(2x² + 3)
(f · g)(x) = 4x(2x² + 3) - 1(2x² + 3)
(f · g)(x) = 4x(2x²) + 4x(3) - 1(2x²) - 1(3)
(f · g)(x) = 8x³ + 12x - 2x² - 3

(f/g)(x)
(f/g)(x) = 4x - 1
             2x² + 3

(g/f)(x)
(g/f)(x) = 2x² + 3
               4x - 1
(g/f)(x)= ¹/₂x + ¹/₈ +  3¹/₈
                              4x - 1
Your engagement is important to us. Keep sharing your knowledge and experiences. Let's create a learning environment that is both enjoyable and beneficial. IDNLearn.com is committed to providing accurate answers. Thanks for stopping by, and see you next time for more solutions.